To Study the Knowledge Levels of Beneficiaries for Pradhan Mantri Ujjawala Yojana in Bundelkhand Region of Uttar Pradesh - Ajay pratap singh; R. K. Doharey; N. R. Meena; Dr. Abhinav Singh; Dr. Ritesh Singh; Anurag Dixit (The Bioscan, 2025)
The present study is going to conduct in the Bundelkhand region of the Uttar Pradesh, particularly study was conducted in four districts namely; Banda, Jhansi, Mahoba and Chitrakoot during 2024-2025, 640 beneficiaries selected from 4 district, 16 blocks were selected randomly. Thus, total numbers of 16 blocks were selected for the study area. From each block, 4 villages were selected randomly. Thus, total numbers of 64 Villages were selected for the study. From each village, ten beneficiaries were selected randomly. The study aimed to assess the knowledge levels of various Particular statements related to Pradhan Mantri Ujjawala Yojana like Not knowledge about LPG cylinder as a cooking fuel?, Not knowledge about application process for getting connection? etc. The findings reveal that 48.44% of Ujjwala beneficiaries had a medium level of knowledge, followed by 41.56% who exhibited a high level of knowledge regarding the scheme. Only 10.00% of the respondents were found to have a low level of knowledge.